Disputes about Platonic legacy of Władysław Witwicki (1878—1948) - Mróz, Tomasz (Folia Philosophica, 2017)
The paper discusses shortly the reception of W. Witwicki’s translations and commentaries to Plato’s dialogues. The emphasis is laid on the initial absence of philosophers among the reviewers of Witwicki’s works, for the overwhelming majority of the reviewers consisted of philologists and writers. In the course of time, when translations by other scholars appeared, Witwicki’s works gained wider reception among professionals and many critical assessments, which were sometimes unjust. His translations, nevertheless, still play a protreptic role as the first.